Process Research in the Ivory Tower - Nathaniel S. Finney (CHIMIA, 2006)
Despite widespread perception to the contrary, training in process chemistry research can be incorporated seamlessly into the academic environment. The challenges and benefits associated with establishing a process research laboratory at the University of Zurich are discussed, and this program is presented as a successful model for expanding the educational mission of the University to include training in process chemistry.